ANALISIS FAKTOR YANG MAMPU MEMPREDIKSI KONDISI FINANCIAL DISTRESS PADA BANK GO PUBLIC PERIODE 2007-2011 - Emil Pratiwi; Luciana Spica Almilia (Jurnal Bisnis dan Ekonomi, 2014)
Financial distress precedes bankruptcy. Most financial distress models actually rely on bankruptcy data, which is easier toobtain. The purpose of this research to examine financial ratios that affect financial distress condition of a bank. Theindependen variable which is used to test on research is CAR, NPL,ROA, ROE, LDR,and IRR. The sample of this researchconsist of 100 banks, chosen by purposive sampling. The statistic method which is used to test on the research hypothesis islogistic regression. This research used 7 logistic regression model from Zaki’s research had developed.The result showthat NPL, ROA, and ROE is a significant variable to determine of financial distress banks.Keywords: financial distress, financial ratios, logistic regression, bankruptcy.